Tren Penelitian Green Entrepreneurship dalam Dekade Terakhir (2016–2026): Analisis Bibliometrik dan Agenda Riset Masa Depan - Rizki Ananda (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2026)
The development of global environmental sustainability issues demands a transformation of business paradigms from conventional profit orientation toward eco-friendly practices through green entrepreneurship. This study aims to map the development trends of publications, identify the intellectual structure of research, and formulate research gaps and future research agendas related to green entrepreneurship over the last decade (2016–2026). Applying a descriptive quantitative method based on bibliometric analysis, metadata of 150 scientific journal articles were extracted from the Google Scholar database using Publish or Perish (PoP) software and visualized using VOSviewer. The results of the analysis indicate a significant increase in annual publications, peaking in 2023. The intellectual structure of the research is divided into three main clusters: (1) macro-policy dimensions and circular economy; (2) the role of vocational/vocational higher education in building green entrepreneurial intentions; and (3) micro-level green product innovation in the MSME sector. Overlay visualization analysis reveals a shift in research focus from basic concepts of environmental management toward the integration of cutting-edge digital technologies such as Artificial Intelligence (AI) and the digitalization of green businesses. These findings provide a theoretical contribution in the form of a systematic research roadmap and practical implications for vocational education institutions in formulating green skills-based entrepreneurship curricula